A study on the macroeconomic effect to the profitability of Bank Islam Malaysia Berhad / Muhammad Hafiz Zaini - Zaini, Muhammad Hafiz (Faculty of Business and Management, Universiti Teknologi MARA, 2011)
In most of the Muslim countries, Islamic banks are operating side by side with conventional banks. Using bank data of Bank Islam Malaysia Berhad (BIMB), this research intends to investigate the effect of macroeconomic variable to the BIMB profitability, during the period 2002 to 2009. The bank level data are obtained from annual report of BIMB. In this study, the ratio to represent the bank profitability is return on asset (ROA) and three variables are used as independent variable that is inflation rate, interest rate (BLR), and gross domestic product (GDP). This study found a significant relationship between profitability measures of Islamic banks with inflation and gross domestic product (GDP). However, the interest rate was found that there are no significant relationships with Bank Islam profitability